Early Detection Basal Stem Rot (BSR) using Electrical Capacitance Tomography (ECT) - Amalludin, Nurul Syuhada (Universiti Teknologi PETRONAS, 2016)
The main purpose of this project is to study the method of Electrical Capacitance Tomography (ECT) for early detection on Basal Stem Rot (BSR) of Palm Oil Tree. BSR is the effect caused by the Ganoderma Boninense, a fungi species. The early detection is important to save the production of the tree. For this preliminary studies, the student used the selected trunk of the palm oil tree as the sample. And the technique called Electrical Capacitance Tomography (ECT) will be used to scan and analyse the behaviour of the trunk. This process is conducted in the lab at Block 23, UTP. The result will confirm either the plant is infected with the Ganoderma disease or not. In this project, the hollowness of the trunk will be demonstrated in tomography form by the data acquisition device provided, the colour of tomography will indicate the healthiness of the tree.